2012
DOI: 10.1260/1369-4332.15.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Structural Behavior of Waffle-Shaped Precast Concrete Panels for Floor Systems

Abstract: A waffle-shaped precast concrete panel named WAS has been newly developed as a floor system. Compared to the conventional double tee (DT), the WAS has a more spacious connection area between the panels while having a shallower depth, which possibly results in an enhanced performance of the connection. Experimental studies were performed to examine the flexural behavior of the WAS according to several primary parameters: the panel types, prestress levels applied to the panels, panel sizes, and the existence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The shear capacity of precast-prestressed deep HCSs was experimentally and numerically investigated by Brunesi et al (2015). Test investigation of new-type waffle-shaped precast concrete slabs (WASs) was performed by Cho et al (2012). They compared the structural behavior of WASs with DTSs and found that the flexural capacity of WASs and DTSs was similar.…”
Section: Introductionmentioning
confidence: 99%
“…The shear capacity of precast-prestressed deep HCSs was experimentally and numerically investigated by Brunesi et al (2015). Test investigation of new-type waffle-shaped precast concrete slabs (WASs) was performed by Cho et al (2012). They compared the structural behavior of WASs with DTSs and found that the flexural capacity of WASs and DTSs was similar.…”
Section: Introductionmentioning
confidence: 99%